2022
DOI: 10.3389/fnsys.2022.916237
|View full text |Cite
|
Sign up to set email alerts
|

Community Exercise: A New Tool for Personalized Parkinson’s Care or Just an Addition to Formal Care?

Abstract: Physiotherapy and exercise are associated with motor and non-motor benefits in Parkinson’s disease (PD). Community exercise programs may increase ongoing exercise participation and help people with Parkinson’s disease actively participate in their health management. But there is still limited knowledge about these programs regarding their benefits, safety, implications over the long-term, and effective implementation. These questions could hold relevant clinical implications. In this perspective article, we id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…At an institutional level, healthcare systems that offer this type of treatment are encouraged to increase the availability of community programs that allow individuals to benefit from these interventions (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At an institutional level, healthcare systems that offer this type of treatment are encouraged to increase the availability of community programs that allow individuals to benefit from these interventions (4).…”
Section: Discussionmentioning
confidence: 99%
“…From a financial perspective, it is suggested that evidence-based practices, including DTT, should be covered as a health insurance benefit. This ensures that DTT is recognized as a viable treatment option and included in the insurance coverage (4,48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative research involving participants and those supporting participation (e.g., spouses) can provide critical insights into the factors that support initiating and maintaining regular exercise. While previous studies have used such methods [26,33,34], there is limited understanding of the perceptions and experiences of PwP and their partners in exercise programmes delivered through a community-university partnership approach [26,35]. Insights generated from these discussions can support the planning, feasibility, and long-term sustainability of exercise programmes for PwP.…”
Section: Introductionmentioning
confidence: 99%
“…It is vital to develop novel therapeutic approaches that are technically feasible, economically valuable, and culturally, ethically, and socially accepted for addressing fall risk and the FOF among this population ( 14–16 ).…”
Section: Introductionmentioning
confidence: 99%